The natural bitumen additive Selenizza® SLN: A promising alternative for producing high-performance asphalt mixes - Edith Tartari (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2021)
The purpose of this paper is to highlight the benefits of using natural bitumen in the context of global environmental change and increasing transportation demands in terms of traffic volume and loads. Despite the advantages of using these additives as binder modifiers to implement high modulus asphalt mixes characterized by high stiffness, high durability, superior resistance to permanent deformation, and good fatigue resistance, they remain still largely unknown and far from being effectively exploited. The paper displays for the first time a collection of scientific data based on previously published research works, enriched by new laboratory testing, whose results are not published yet. It aims to provide a comprehensive understanding of various aspects of the natural bitumen Selenizza® (extracted from the deposit located in southeast Albania) and the role that this natural additive plays in achieving the desired asphalt pavement performance. The dynamic rheological and Modulated Differential Scanning Calorimetry (MDSC) analysis proved that natural bitumens are fully compatible with straight-run bitumen and contribute to increasing the consistency, viscosity, and stability of natural bitumen-modified binders. The Rolling Thin-Film Oven Test (RTFOT), followed by Pressure Aging Vessel (PAV) aging analysis of road bitumen modified with Selenizza®, revealed that the resulting binders are resistant to aging and relatively efficient at low temperatures.  A Life Cycle Assessment study compared the environmental impact of the Albanian natural bitumen production process with that of conventional crude oil bitumen, leading to the conclusion that the CO2 emission released during the production of Selenizza® is reduced by approximately 44 % compared to that of crude oil bitumen. The various research works described in this paper provide evidence that the natural bitumen-based asphalt mixes feature enhanced quality in terms of mechanical and rheological properties compared to reference asphalt mixes produced with equivalent traditional paving grade bitumen.